Osteopontin as a candidate of therapeutic application for the acute brain injury - Zhou, Yunxiang (J Cell Mol Med, 2020)
Acute brain injury is the leading cause of human death and disability worldwide, which includes intracerebral haemorrhage, subarachnoid haemorrhage, cerebral ischaemia, traumatic brain injury and hypoxia‐ischaemia brain injury. Currently, clinical treatments for neurological dysfunction of acute brain injury have not been satisfactory. Osteopontin (OPN) is a complex adhesion protein and cytokine that interacts with multiple receptors including integrins and CD44 variants, exhibiting mostly neuroprotective roles and showing therapeutic potential for acute brain injury. OPN‐induced tissue remodelling and functional repair mainly rely on its positive roles in the coordination of pro‐inflammatory and anti‐inflammatory responses, blood‐brain barrier maintenance and anti‐apoptotic actions, as well as other mechanisms such as affecting the chemotaxis and proliferation of nerve cells. The blood OPN strongly parallel with the OPN induced in the brain and can be used as a novel biomarker of the susceptibility, severity and outcome of acute brain injury. In the present review, we summarized the molecular signalling mechanisms of OPN as well as its overall role in different kinds of acute brain injury.